Pengaruh Persepsi dan Minat Belajar Matematika Siswa dalam Pembelajaran Daring Terhadap Hasil Belajar Matematika - Mersi Lumuly; Christina Martha Laamena; Theresia Laurens (Jurnal Padegogik, 2022)
This study aims to determine the effect of student perceptions and student interest in online learning on mathematics learning outcomes. The research method is causal design with a sample of 26 students determined by random sampling (randomly). The population in this study was students of class X SMA Negeri 14 Ambon in the academic year 2020/2021.  The research instrument used a questionnaire and a test, for a student perception questionnaire totaling 25 statement items, for a student learning interest questionnaire totaling 29 statement items. Data analysis used normality test, simple regression analysis and multiple regression which contained linearity test, correlation coefficient, determinant coefficient, t-test and F-test at a significant level = 0.05 with the help of SPSS ver. 25.0. Based on the results of the study, it was concluded that there was no effect of students' perceptions and student interest in online learning on the mathematics learning outcomes of class X SMA Negeri 14 Ambon. The contribution of students' perceptions and interest in learning to learning outcomes is 27% and the remaining 73% is influenced by other variables.